Development of Interactive Physics Mobile Learning Media for Enhancing Students’ HOTS in Impulse and Momentum with Scaffolding Learning Approach - Erlin Eveline; Suparno Suparno; Tiara Kusuma Ardiyati; Beatrix Elvi Dasilva (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
The study objectives are to (1) produce an android-based Interactive Physics Mobile Learning Media (IPMLM) product in impulse and momentum material that is feasible to improve higher-order thinking skills (HOTS) of high school students; (2) know the effectiveness of android-based IPMLM in impulse and momentum material with a scaffolding approach toward HOTS of high school students. This research was Research and Development (R&D) with a 4D model. The development steps were: (1) Defining, including needs analysis activities; (2) Designing, the selection and design of research instruments and IPMLM activities; (4) Developing, an activity of developing research instruments and IPMLM, assessment of the feasibility of learning instruments, validation of research instruments, and assessment of the feasibility of IPMLM by experts, limited tests, and extensive tests; (4) Disseminating, an IPMLM dissemination activity. IPMLM feasibility assessment was carried out to determine the feasibility of IPMLM. Products that have been assessed by experts were further limited and extensively tested. The limited test subjects consisted of 13 students in the SMA Yayasan Pendidikan Kristen, Pontianak, while the extensive test subjects consisted of 48 students in SMA Koperasi Pontianak. The results show: (1) IPMLM is feasible to be used for enhancing students’ HOTS with “very feasible” criteria based on expert judgment; (2) IPMLM is effective for enhancing students' HOTS. The learning process assisted by IPMLM media with a scaffolding approach can help student complete tasks in the HOTS aspect and improve learning with 21st-century learning-based activities.